Current Perspectives and Potential of Probiotics to Limit Foodborne Campylobacter in Poultry - Deng, Wenjun; Dittoe, Dana K.; Pavilidis, Hilary O.; Chaney, William E.; Yang, Yichao; Ricke, Steven C. (Frontiers in Microbiology, 2020)
Poultry has been one of the major contributors of Campylobacter related human foodborne illness. Numerous interventions have been applied to limit Campylobacter colonization in poultry at the farm level, but other strategies are under investigation to achieve more efficient control. Probiotics are viable microbial cultures that can establish in the gastrointestinal tract (GIT) of the host animal and elicit health and nutrition benefits. In addition, the early establishment of probiotics in the GIT can serve as a barrier to foodborne pathogen colonization. Thus, probiotics are a potential feed additive for reducing and eliminating the colonization of Campylobacter in the GIT of poultry. Screening probiotic candidates is laborious and time-consuming, requiring several tests and validations both in vitro and in vivo. The selected probiotic candidate should possess the desired physiological characteristics and anti-Campylobacter effects. Probiotics that limit Campylobacter colonization in the GIT rely on different mechanistic strategies such as competitive exclusion, antagonism, and immunomodulation. Although numerous research efforts have been made, the application of Campylobacter limiting probiotics used in poultry remains somewhat elusive. This review summarizes current research progress on identifying and developing probiotics against Campylobacter and presenting possible directions for future research efforts.